AKT 3 Induced Hepatitis: Case Report - Sajan, Cyril; Shah, Priyanshi Rakesh; Mistry, Mahek (Journal of Pharmacy Practice and Community Medicine)
As tuberculosis is a global health problem. Non-adherence related to treatment regimen and inappropriate prescription of tuberculosis therapy may be one of the major contributing factors in public health. Hepatotoxicity is leading adverse effect of first line anti tuberculosis medication. They do not cause hepatotoxicity in all patients but there are many reported cases which showed hepatotoxicity due to antituberculosis drugs. This adverse effect occurs due to individual drug metabolize by alternative pathways. A 24-year-old female came to respiratory department with complains of dry cough and generalized weakness since one month, pedal edema for three days, breathlessness, chest pain and weight loss. She was known case of systemic lupus erythematosus with vitamin B12 deficiency with Hypothyroidism. She had recurrent tuberculosis in the last 15 days and for that she was put on isoniazid, rifampicin, ethambutol, pyrazinamide combination (HRZE regimen). Her laboratory reports suggest she developed hepatitis for which antituberculosis drugs were suspected. She was put on alternative regimen (streptomycin, levofloxacin, ethambutol and ethambutol). After stopping potent hepatotoxic medication, she started reliving symptoms of hepatitis. The early diagnosis of reaction and close monitoring of patient prevented the seriousness of reaction in this case.
Keywords: Tuberculosis; Anti Koch Therapy; Hepatotoxicity; Isoniazid; Rifampin.